1992
DOI: 10.1007/bf01192311
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of the use of 17?-N,N-diethylcarbamoyl-4-methyl-4-aza-5-?-androstan-3-one (4MA), a 5?-reductase inhibitor, in prostate cancer therapy

Abstract: We investigated the effect of 17 beta-N,N-diethylcarbamoyl-4-methyl-4aza- 5 alpha-androstan-3-one (4MA), a 5 alpha-reductase inhibitor, on growth inhibition of androgen-sensitive rat prostatic tumour (R3327-H) and correlated it with changes in weight of normal androgen target tissues and with levels of androgens. Groups of male Copenhagen rats were treated for 28 days with a daily injection of various, increasing doses of 4MA (0.01-4.0 mg/day) and the results were compared with control (vehicle-treated) and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The immunohistochemical staining of BrdUrd-incorporating cells has been described before (Geldof et al 1992). Briefly, cells were fixed in acetone ( -20 ~ and sequentially incubated in formamide/citrate to hydrolyse DNA, with monoclonal anti-BrdUrd antibody and with secondary rabbit antimouse peroxidase they were then stained with diaminobenzidine (metal-enhanced DAB, Pierce, Rockford, USA).…”
Section: Bromodeoxyuridine (Brdurd) Incorporation Assaymentioning
confidence: 99%
“…The immunohistochemical staining of BrdUrd-incorporating cells has been described before (Geldof et al 1992). Briefly, cells were fixed in acetone ( -20 ~ and sequentially incubated in formamide/citrate to hydrolyse DNA, with monoclonal anti-BrdUrd antibody and with secondary rabbit antimouse peroxidase they were then stained with diaminobenzidine (metal-enhanced DAB, Pierce, Rockford, USA).…”
Section: Bromodeoxyuridine (Brdurd) Incorporation Assaymentioning
confidence: 99%
“…This altered responsiveness of the HPA axis to stress in pregnancy is induced by the actions of allopregnanolone on the brain. Thus blocking allopregnanolone production in pregnant rats with overnight administration of either finasteride (a 5α-reductase inhibitor, which has been shown to reduce brain allopregnanolone content by up to 90%) (Concas et al, 1998) or 4-MA (17β-(N,N-diethyl)carbamoyl-4-methyl-4-aza-5α-androstan-3-one) (Geldof et al, 1992) substantially restores HPA axis responses to physical and emotional stressors (Brunton et al, 2009) (Ma S and Russell JA, unpubl.). Moreover, in males and non-pregnant females, peripheral allopregnanolone administration suppresses HPA axis responses to stress (Brunton et al, 2009;Patchev et al, 1996).…”
Section: Role Of Allopregnanolone In Hpa Axis Hyporesponsiveness In Pmentioning
confidence: 99%
“…1) have also shown effectiveness in vitro and in vivo. [11][12][13][14] In previous studies, 15) we found that the C-4 chloro analog combined with a C-17 benzoyloxy group on the progesterone skeleton exhibited a higher antiandrogenic activity than the C-4 bromo compound. This phenomenon could probably be explained by taking into consideration the higher electronegativity of C-4 chlorine atom as compared to the C-4 bromo compound.…”
mentioning
confidence: 99%